2022
DOI: 10.3389/fphys.2022.862207
|View full text |Cite
|
Sign up to set email alerts
|

Resting State EEG Directed Functional Connectivity Unveils Changes in Motor Network Organization in Subacute Stroke Patients After Rehabilitation

Abstract: Brain plasticity and functional reorganization are mechanisms behind functional motor recovery of patients after an ischemic stroke. The study of resting-state motor network functional connectivity by means of EEG proved to be useful in investigating changes occurring in the information flow and find correlation with motor function recovery. In the literature, most studies applying EEG to post-stroke patients investigated the undirected functional connectivity of interacting brain regions. Quite recently, work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Indeed, brain network reorganization has been demonstrated to depend on time after stroke [ 84 ], and an increase in inter-hemispheric connectivity, particularly between the primary motor cortexes in alpha and beta frequencies, was found to positively correlate with motor outcome improvement [ 71 , 82 , 83 ]. Conversely, an increase in RS-directed connectivity measures, from pre-motor towards primary motor intra-hemispheric regions, was found in sub-acute patients assessed before and after rehabilitation treatment [ 85 ]. Hoshino et al in 2021 found higher intra-hemispheric FC in both hemispheres in RS and during ankle movement [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, brain network reorganization has been demonstrated to depend on time after stroke [ 84 ], and an increase in inter-hemispheric connectivity, particularly between the primary motor cortexes in alpha and beta frequencies, was found to positively correlate with motor outcome improvement [ 71 , 82 , 83 ]. Conversely, an increase in RS-directed connectivity measures, from pre-motor towards primary motor intra-hemispheric regions, was found in sub-acute patients assessed before and after rehabilitation treatment [ 85 ]. Hoshino et al in 2021 found higher intra-hemispheric FC in both hemispheres in RS and during ankle movement [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…The normalized DTF was used for assessing directed functional connectivity from EEG recordings in one subject who received a new prosthodontic provisional implant as a substitute for previous dental repairs [ 169 ]. DC and gPDC were exploited to investigate the changes in resting-state directed connectivity associated with sensorimotor rhythms and , occurring in stroke patients who followed a rehabilitation treatment [ 170 ]. The results suggest that using different methods to measure directed connectivity can improve the understanding of how brain motor regions are connected between each other.…”
Section: Functional Connectivity Estimation Approachesmentioning
confidence: 99%
“…Finally, EEG connectivity appears to be locally impaired in chronic stroke, with significant modifications in connectivity from the subacute to the chronic stage ( 83 ). In the chronic phase, the reduction of the beta band (12.5–30.0 Hz) oscillatory activity in the motor cortex is an index of motor impairment ( 84 ).…”
Section: Neurophysiological Changes During the Chronic Phasementioning
confidence: 99%